Pengaruh Selebgram Muslimah terhadap Perilaku Konsumtif Mahasiswi (Studi Kasus Mahasiswi Sekolah Tinggi Ekonomi Syariah Islamic Village Tangerang Banten) - Sunardi Sunardi; Wiwi Juansyah (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2021)
AbstractThis study aims to determine whether there is an effect of Muslimah program on female student consumptive behavior in online shopping at the Islamic Village Islamic School of Economics. The variables used in this study were the Muslimah program (X) and consumptive behavior (Y). This study uses a quantitative approach. The population of this study were all active students of the Islamic Village Islamic School of Economics with a sample of 66 female students. Sampling was done using simple random sampling technique, namely random sample selection without considering existing positions in the population. The results showed that there was an influence of Muslimah program on the consumptive behavior of Islamic Village Islamic Economics College students in shopping online. This is evidenced by using the t test which shows that the t count is 5.083 with the t table of 1.66901. It can be concluded that t is greater than t table, which means that Ho is rejected and Ha is accepted, so that there is an influence between Muslimah programs on female student consumptive behavior. When viewed from a simple regression analysis, it shows that Y = (0.7166) + 0.378X and the correlation coefficient value is 0.537 and the coefficient of determination is 0.288 or 28.8%. This means that the Muslimah program has an influence on female student consumptive behavior in online shopping amounting to 28.8% while 71.2% is influenced by other factors. Thus, Muslimah programs have a positive effect on student consumptive behavior in online shopping.Keywords: Instagram, Muslim Celebrities, Consumptive Behavior.